Gender inequities in global health: Insights from Ghana’s National Health Insurance Scheme - Anita Bans-Akutey (Annals of Management and Organization Research, 2025)
Purpose: This systematic review examines gender inequities in global health and critically analyzes how these inequities manifest within Ghana’s National Health Insurance Scheme (NHIS), drawing on the Gender and Development (GAD) theoretical framework. Methodology/approach: This study followed PRISMA 2020 guidelines, for systematic reviews to select thirty-seven articles from major databases. Thematic synthesis was applied to identify recurring patterns. Results/findings: Findings showed that globally, gender inequities in health systems were linked to women’s economic dependency, sociocultural norms, and limited decision-making autonomy. Within Ghana’s NHIS, these inequities manifested through lower enrollment and renewal rates among women, affordability challenges for informal sector workers, and barriers tied to cultural norms that restrict autonomy in healthcare utilization. While maternal health exemptions improved access, they were insufficient to address deeper structural inequalities. Conclusion: This study concludes that Ghana’s NHIS, though designed to promote universal coverage, often replicate broader gender inequities unless deliberate structural reforms are integrated. Limitations: The focus on Ghana as a case, while illustrative, also limits the transferability of findings to other national health systems with differing socio-cultural and policy contexts. Contribution: This review advances scholarship by applying the GAD framework to emphasize the structural and relational barriers that must be addressed for truly gender-responsive health policy.